STUDI PERUBAHAN SIFAT FISIK TANAH DAN HASIL JAGUNG MANIS (ZEA MAYS SACCHARATA STURT) PADA INCEPTISOL YANG DIBERIKAN KASCING - NI MADE TRIGUNASIH; TATIEK KUSMAWATI (Agrotrop : Journal on Agriculture Science, 2011)
Study of Casting Fertilizers on Physical Properties Change of Soil and Yield of Sweet Corn on Inceptisol. A field experiment was conducted to study the effect of casting fertilizes on soil physical characteristics and yield of sweet corn (Zea mays saccharata Sturt) on Inceptisol. The Experiment was arranged in Randomized Block Design (RBD) with three replications and eight treatments. The treatments were consisted of : O0 = control (without casting); O1 = 2.5 ton/ha; O2 = 5 ton/ha; O3 = 7.5 ton/ha; O4 = 10 ton/ha; O5 = 12.5 ton/ha; O6 = 15 ton/ha; O7= 17.5 ton/ha. The results indicated that casting fertilizer was highly significant affected on soil conductivity and soil aggregates, but was not significant to soil porosity, and fresh corn cob weight of the yield. The casting fertilizer rate of 15 to ha- 1 gave the highest yield of 13.69 ton ha-1 or increasing of 60.12% compared to without casting fertilizer (8.55 ton ha-1). The treatment casting of 15 ton ha-1 could increase soil conductivity of 480.87% (20.97 cm/hours compared with control (3.61 cm/hours) and the soil aggregate could increase of 150.16% (3.53 ml) compared to control (1.26 ml).